Clinical and Imaging Study of Repetitive Transcranial Magnetic Stimulation in the Treatment of Morphine Dependence Through mGluR5/TDP43/NR2B Pathway. (20th October 2021) - Li, Xin; Li, Congyan; Yu, Jia'nan; Ji, Qing; Wang, Wei; Peng, Ying; Zhu, Xiaofeng; Liu, Jiguang
Abstract : Morphine is tolerable after long-term use. After long-term use, it will have a great impact on the human body, and the treatment effect is not good. In recent years, the continuous development of repetitive transcranial magnetic stimulation (rTMS) treatment technology has made a treatment. Drug-resistant morphine dependence has a breakthrough. In this article, to study the effect of repeated transcranial magnetic stimulation in the treatment of morphine dependence through mGluR5/TDP43/NR2B pathway, experiments were carried out on rats to compare the changes in the images of rats after different periods of morphine use and their effects on morphine withdrawal. During the period, the performance of rats provides a reference for repeated transcranial stimulation to treat morphine dependence. According to the experimental results, after stopping morphine, withdrawal from the rats, irritable acts, and patience diminished. This is a decrease of more than 50% in comparison with the one of the normal group. There was a different degree of variability in the treatment images of mGluR5/TDP43 and so on after rTMS treatment, and the changes were large. These reductions in detoxification responses in rodents suggest that rTMS serves an instrumental role in the prevention and treatment of phosphorylation related to morphine dependence.